State-Space Cointegration Modeling for the Analysis of Exogenous Shocks to Prices in Israeli-Palestinian Food Trade - Rico Ihle; Linde Götz; Ofir D. Rubin (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
The Israeli-Palestinian conflict constitutes a prominent example of a long-lasting political conflict which has major consequences for the livelihoods of the people on both sides. The agricultural sectors of the Palestinian and Israeli economies are tightly connected. However, various security measures occasionally implemented in consequence of the political conflict between Israelis and Palestinians strongly inhibit the movement of people and commodities. In order to obtain evidence on the impacts of such abrupt trade impediments on price dynamics, we estimate a vector error correction model in state space form employing the Kalman filter. The time-varying cointegration parameters suggest that the security measures indeed impacted price interdependencies on a short-term scale.
Keywords: C32; D74; Q11; Q13; F15; 330; cointegration; error correction; Israel; Palestinian territories; price transmission; state space model; time-varying parameters